The effectiveness of resistance training in children: A meta-analysis - Falk, B.; Tenenbaum, G. (Sports Medicine, 1996)
Early studies and theorists have generally supported the view that resistance (strength) training in prepubescent children is ineffective. This study performed a meta-analysis on published studies that used Ss with a maximum age of 12 yr for girls and 13 yr for boys.